Analysis of Signals Leading to Differentiation of Immature HL-60 after Administration of IL-4 - Simon Vassiliadis (Mediators of Inflammation)
Treatment of acute myeloid leukaemia (AML) cells with differentiation agents leads not only to the acquisition of normal phenotypes but also contributes to the understanding of special immuno-haematology issues. For instance, induction of HLA-DR antigens on human promyelocytic leukaemia HL-60 cells by interleukin-4 (IL-4) is of pivotal importance in immunology not only because class II expression is prerequisite to antigen recognition and response but also because IL-4 participates in a plethora of inflammatory or non-inflammatory reactions. At the same time, the same observation coupled with an increase in Mac-1, mature monocyte marker, is revealing ways to haematologists for converting malignant cases to normal situations. Based on previous reports that HLA-DR induction by IL-4 in the HL-60 system is mediated via the G-protein system (p21ras), this study was undertaken in order to define the intermediate signalling steps followed by this agent from the moment it is added to cultures to the differentiated cellular form obtained. It is proposed that IL-4 increases p21ras which in turn suppresses the HL-60 cells' p34cdc2 constitutive expression. This inhibition appears to be responsible for the subsequently.observed cessation ofgrowth. Concomitant to decreased cellular proliferation, HI-DR antigen expression increases, a finding that matches the initially mentioned induction of p21ras since its inhibition abolishes HI-DR upregulation.